Targeting LOX‐1 in atherosclerosis and vasculopathy: current knowledge and future perspectives. Issue 1 (1st November 2018) - Tian, Kunming; Ogura, Sayoko; Little, Peter J.; Xu, Suo‐wen; Sawamura, Tatsuya
Abstract: LOX‐1 (lectin‐like oxidized low‐density lipoprotein receptor‐1; also known as OLR1) is the dominant receptor that recognizes and internalizes oxidized low‐density lipoproteins (ox‐LDLs) in endothelial cells. Several genetic variants of LOX‐1 are associated with the risk and severity of coronary artery disease. The LOX‐1–ox‐LDL interaction induces endothelial dysfunction, leukocyte adhesion, macrophage‐derived foam cell formation, smooth muscle cell proliferation and migration, and platelet activation. LOX‐1 activation eventually leads to the rupture of atherosclerotic plaques and acute cardiovascular events. In addition, LOX‐1 can be cleaved to generate soluble LOX‐1 (sLOX‐1), which is a useful diagnostic and prognostic marker for atherosclerosis‐related diseases in human patients. Of therapeutic relevance, several natural products and clinically used drugs have emerged as LOX‐1 inhibitors that have antiatherosclerotic actions. We hereby provide an updated overview of role of LOX‐1 in atherosclerosis and associated vascular diseases, with an aim to highlighting the potential of LOX‐1 as a novel theranostic tool for cardiovascular disease prevention and treatment. Abstract : This article provides an updated overview of the role in atherosclerosis (and associated vascular diseases) of LOX‐1 (lectin‐like oxidized low‐density lipoprotein receptor‐1), the main receptor for the uptake of oxidized low‐density lipoproteins in endothelial cells. It also highlights the potential of LOX‐1 as a novel theranostic tool for cardiovascular disease prevention and treatment.